2008
DOI: 10.1002/ana.21511
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and NADPH oxidase drive neuronal superoxide formation in stroke

Abstract: Objective Hyperglycemia has been recognized for decades to be an exacerbating factor in ischemic stroke, but the mechanism of this effect remains unresolved. Here we evaluated superoxide production by neuronal NADPH oxidase as a link between glucose metabolism and neuronal death in ischemia-reperfusion. Methods Superoxide production was measured by the ethidium method in cultured neurons treated with oxygen-glucose deprivation and in mice treated with forebrain ischemia-reperfusion. The role of NADPH oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
202
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 254 publications
(216 citation statements)
references
References 45 publications
(61 reference statements)
11
202
0
3
Order By: Relevance
“…Thirty minutes of ischemia induced substantial neuronal death in the hippocampus. The pattern and the degree of neuronal death in the wild-type mice are similar to that reported previously (Suh et al, 2008a). Hippocampal neuronal death was significantly higher in the EAAC1 Ϫ/Ϫ mice in the CA1, subiculum, dentate gyrus, and hilus (Fig.…”
Section: Increased Neuronal Death In Eaac1supporting
confidence: 88%
See 1 more Smart Citation
“…Thirty minutes of ischemia induced substantial neuronal death in the hippocampus. The pattern and the degree of neuronal death in the wild-type mice are similar to that reported previously (Suh et al, 2008a). Hippocampal neuronal death was significantly higher in the EAAC1 Ϫ/Ϫ mice in the CA1, subiculum, dentate gyrus, and hilus (Fig.…”
Section: Increased Neuronal Death In Eaac1supporting
confidence: 88%
“…The common carotid arteries were encircled with a 4/O silk suture before the start of the occlusion. Small aneurismal clips were applied to both common carotid arteries for 30 min of occlusion (Suh et al, 2008a). Core temperature was kept at 36.5-37.5°C with a homoeothermic blanket control unit (Harvard Apparatus).…”
Section: Mouse Colonies Eaac1mentioning
confidence: 99%
“…23,24 Of note, glucose availability can be rate-limiting for NADPH production, and thus for superoxide production, and this provides a mechanism by which hyperglycemia can exacerbate injury during ischemia or inflammation. 25,26 Recent work has shown that microglia can potentiate injury to blood-brain barrier constituents (astrocytes and endothelial cells) via NOX-mediated superoxide in cell culture models of ischemia. 13 In addition, several groups have shown that mice deficient in the gp91 subunit of NOX2 have smaller infarcts than do wild-type mice, [27][28][29] and that outcomes from experimental cerebral ischemiareperfusion are improved with early administration of the pharmacological NOX inhibitors apocynin 29 -33 and honokiol.…”
Section: Superoxide Productionmentioning
confidence: 99%
“…34,35 These results identify NOX as a promising target for therapeutic intervention, but it is possible that the efficacy of these treatment strategies may be due largely or in part to inhibition of NOX in cell types other than microglia. 25 There are as yet no published studies addressing the efficacy of NOX inhibitors administered at delayed time points after ischemia, in a manner selectively targeting the inflammatory response.…”
Section: Superoxide Productionmentioning
confidence: 99%
“…We have termed this process 'glucose reperfusion-induced neuronal death' after hypoglycemia (Suh et al, 2007). This hypothesis is also applicable in ischemia-reperfusion-induced neuronal death (Suh et al, 2008b). Currently, the only available method for preventing this hypoglycemiainduced neuronal death in the clinical setting is delivery of glucose; a treatment that paradoxically may actually exacerbate the insult.…”
Section: Introductionmentioning
confidence: 99%